Re-analysis of gene mutations found in pituitary stalk interruption syndrome and a new hypothesis on the etiology - Wang, Shengjie; Qin, Qiaozhen; Jiang, Deyue; Xiao, Yan; Ye, Lingtong; Jiang, Xiaoxia; Guo, Qinghua (Frontiers in Endocrinology, 2024)
Background Pituitary stalk interruption syndrome (PSIS) is a complex clinical syndrome characterized by varied pituitary hormone deficiencies, leading to severe manifestations across multiple systems. These include lifelong infertility, short stature, mental retardation, and potentially life-threatening pituitary crises if not promptly diagnosed and treated. Despite extensive research, the precise pathogenesis of PSIS remains unclear. Currently, there are two proposed theories regarding the pathogenic mechanisms: the genetic defect theory and the perinatal injury theory. Methods We systematically searched English databases (PubMed, Web of Science, Embase) and Chinese databases (CNKI, WanFang Med Online, Sinomed) up to February 24, 2023, to summarize studies on gene sequencing in PSIS patients. Enrichment analyses of reported mutated genes were subsequently performed using the Metascape platform. Results Our study included 37 articles. KEGG enrichment analysis revealed mutated genes were enriched in the Notch signaling pathway, Wnt signaling pathway, and Hedgehog signaling pathway. GO enrichment analysis demonstrated mutated genes were enriched in biological processes such as embryonic development, brain development, axon development and guidance, and development of other organs. Conclusion Based on our summary and analyses, we propose a new hypothesis: disruptions in normal embryonic development, partially stemming from the genetic background and/or specific gene mutations in individuals, may increase the likelihood of abnormal fetal deliveries, where different degrees of traction during delivery may lead to different levels of pituitary stalk interruption and posterior lobe ectopia. The clinical diversity observed in PSIS patients may result from a combination of genetic background, specific mutations, and variable degrees of traction during delivery.